Day 4 Thu, May 08, 2014 2014
DOI: 10.4043/25197-ms
|View full text |Cite
|
Sign up to set email alerts
|

Significant ageing effects for axially loaded piles in sand and clay verified by new field load tests

Abstract: The paper describes key results from a series of new load tests to verify the impact of time or ageing on the axial bearing capacity of driven tubular steel piles. Load tests in two different sand deposits (a silty fine loose sand deposit and a medium dense, medium sand deposit), and four different clay deposits (low and medium plastic normally consolidated clay, over consolidated glacial clay, and a very highly plastic and over consolidated clay) were undertaken. Six tubular test piles were driven at each tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…Based on static and dynamic load tests, the 492 authors proposed that the end of driving shaft capacity of piles was 70% of the resistance predicted 493 using the ICP design method. This proposal was consistent with field tests reported by Gavin et al 494 (2013) and Karlsrud et al (2014) summarised in Gavin et al (2015). For the UWA-05 approach, the 495 base resistance is further modified herein using the base-settlement model in Fig.…”
Section: Unmodified Static Capacity Approaches 462supporting
confidence: 80%
“…Based on static and dynamic load tests, the 492 authors proposed that the end of driving shaft capacity of piles was 70% of the resistance predicted 493 using the ICP design method. This proposal was consistent with field tests reported by Gavin et al 494 (2013) and Karlsrud et al (2014) summarised in Gavin et al (2015). For the UWA-05 approach, the 495 base resistance is further modified herein using the base-settlement model in Fig.…”
Section: Unmodified Static Capacity Approaches 462supporting
confidence: 80%
“…Chow et al (1996) reported an increase in the shaft resistance of open-ended steel piles driven into dense sands. Karlsrud et al (2014) verified significant ageing effects in sand and clay by performing pile load tests. The tensile capacity computed using the ICP method is mobilized about ten days after driving.…”
Section: Imperial Collegementioning
confidence: 73%
“…This time-dependent increase may be due to a chemical process, particularly corrosion, cementation, or creep, which reduces arching effects. The trend reported by Karlsrud et al (2014) could be used to evaluate the increase in shaft resistance in both clay and sand due to ageing. The trend reported by Jardine et al (2005) shown on Figure 3, could be used to evaluate the increase in shaft resistance in sand due to ageing.…”
Section: Imperial Collegementioning
confidence: 99%
“…Simple expressions were developed that captured the above shaft capacity phenomena and also pile end bearing capacity. Subsequent research has considered additional factors, including N the influence of load cycles imposed during installation (White & Lehane, 2004;Jardine et al, 2013a) N time effects (Jardine et al, 2006;Gavin et al, 2013;Karlsrud et al, 2014) N how particle breakage under the tip and surface abrasion affect the stresses and the development of a well-defined interface shear zone (Yang et al, 2010) N the stress regime developed in the surrounding soil mass (Jardine et al, 2009(Jardine et al, , 2013b N the influence of cyclic loading (Tsuha et al, 2012). Yang et al (2014) and Zhang et al (2014) have gone on to relate stress measurements from experimental investigations and numerical analyses by other workers.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 11 piles (from just three sites) were open-ended, had D > 600 mm and full CPT profiles. Further tests are required to augment this sparse dataset, obtain information from a wider range of international sites and gain further insight into uncertain factors such as the effects of layering on base resistance (Xu, 2006) and the effects of pile age on capacity (Jardine et al, 2006;Gavin et al, 2013;Karlsrud et al, 2014).…”
Section: Introductionmentioning
confidence: 99%